Patients’ adherence to antimalarial medication; self-report of patients at the Volta regional hospital of Ho, Ghana - Afaya, Agani; Salia, Solomon Mohammed; Opare, Frederick Yaw; Ali, Samira; Afaya, Richard Adongo (International Journal of Research in Medical Sciences, 2017)
Background: Despite the advancement in malaria treatments and management; malaria morbidity and mortality is still on the increase. This phenomenon has been mostly attributed to the emergence and transmission resistance of the plasmodium parasite to drugs; which is as a result of non-adherence to anti-malaria medication. Therefore, the purpose of this study was to assess patients’ adherence to anti-malarial medications and the factors influencing their adherence in the Volta regional hospital. Methods: A descriptive cross-sectional study was employed. Convenience sampling technique was used in recruiting respondents. Data were collected within a period of 8 weeks from April to May 2017. Data were analyzed using descriptive statistics in the form of frequencies, percentages, mean and standard deviations which was generated by the use of IBM statistical package for social sciences version 23. Results: The average age of respondents surveyed for this study was 32.27±11.09 ranging from of 19 to 68 years. Majority (51.7%) of respondents were females and 76.7% of them being Christians. The study findings revealed that 36.6% of patient were completely adherent to anti-malarial medication. Over 90% of respondents agreed that the malarial medication had bad taste and it was an unpleasant feeling for them taking it. Conclusions: Poor adherence to antimalaria medications could play a role in the future development of drug resistance. As such, identifying ways to improve anti-malarial compliance will help mitigate drug resistance. Therefore, further studies should be carried out on ways to improve patients’ adherence to antimalarial medication.